Association Between the Nutritional Risk and the Survival Rate in Newly Diagnosed GIST Patients - Ding, Ping'an; Guo, Honghai; Yang, Peigang; Sun, Chenyu; Tian, Yuan; Liu, Yang; Li, Yong; Zhao, Qun (Frontiers in Nutrition, 2021)
Background: Currently, the incidence of gastrointestinal stromal tumors (GIST) is increasing rapidly worldwide. Malnutrition may increase the risk of perioperative complications and affect the prognosis of patients. However, the nutritional status of GIST patients and its impact on prognosis have received less attention. Therefore, this study aims to explore the prevalence of malnutrition in newly diagnosed GIST patients, the proportion of participants in need of nutritional intervention, and the relationship between nutritional status and overall survival (OS). Methods: We retrospectively analyzed the clinical data of GIST patients treated in our hospital from January 2014 to January 2018. Nutritional Risk Screening 2002 (NRS2002) and Patient-Generated Subjective Global Assessment (PG-SGA) were used to assess the nutritional status of all patients. This study was to investigate the clinical significance of PG-SGA by analyzing the relationship between PG-SGA score and OS. Results: A total of 1,268 newly diagnosed GIST patients were included in this study, of which 77.76% were at risk of malnutrition (NRS2002 score≥3), and the incidence of malnutrition was 35.88% (PG-SGA score≥4). Meanwhile, we found 13.41% of the patients required urgent nutritional support (PG-SGA score≥9). Multivariate analysis showed that age (p=0.016), BMI (p=0.001), anemia (p=0.010), pre-albuminand (p=0.000), albumin(p=0.000), tumor location(p=0.000), tumor size(p=0.000), and NIH classification(p=0.000) were risk factors for nutritional status. The research outcomes indicated that there was a negative correlation between PG-SGA and various nutritional parameters (p<0.05). The prognosis was significantly different in GIST patients with PG-SGA score at admission (p<0.05). Conclusion: This study suggested that malnutrition is ubiquitous in newly diagnosed GIST patients, and the higher the PG-SGA score, the worse the clinical outcome.